2004
DOI: 10.1111/j.1467-8624.2004.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Child Care in Poor Communities: Early Learning Effects of Type, Quality, and Stability

Abstract: Young children in poor communities are spending more hours in nonparental care because of policy reforms and expansion of early childhood programs. Studies show positive effects of high-quality center-based care on children's cognitive growth. Yet, little is known about the effects of center care typically available in poor communities or the effects of home-based care. Using a sample of children who were between 12 and 42 months when their mothers entered welfare-to-work programs, this paper finds positive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(141 citation statements)
references
References 35 publications
8
128
0
5
Order By: Relevance
“…However, some limitations should be noted: (a) Many studies have documented effects of quality childcare for cognitive outcomes in samples with various socioeconomic backgrounds (Belsky et al, 2007;NICHD ECCRN, 2006), and in samples of disadvantaged children (Loeb, Fuller, Kagan, & Carrol, 2004). Therefore we could expect cognitive measures in children to be more sensitive to childcare quality than to type of childcare arrangement.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, some limitations should be noted: (a) Many studies have documented effects of quality childcare for cognitive outcomes in samples with various socioeconomic backgrounds (Belsky et al, 2007;NICHD ECCRN, 2006), and in samples of disadvantaged children (Loeb, Fuller, Kagan, & Carrol, 2004). Therefore we could expect cognitive measures in children to be more sensitive to childcare quality than to type of childcare arrangement.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, some studies have reported no association between ECE and externalizing problem behavior (Howes et al, 2008;Loeb, Fuller, Kagan, & Carrol, 2004). Loeb, Fuller, Kagan, and Carrol compared outcomes for low-income children between 12 and 42 months who were in ECE programs to similar children cared for by kith or kin and found no effects on externalizing behavior problems.…”
Section: Ece and Externalizing Behavior Problems: An Overviewmentioning
confidence: 99%
“…Correlational studies that statistically control for family background and family SES have also found consistently positive relationships between childcare centers and children's cognitive development, and the effects are largest for children from the most disadvantaged homes Waldfogel 2005, Shonkoff andPhillips 2000). Childcare centers tend to be better than other forms of childcare (such as relative care, non-relative in-home care, or care in another person's home) because the teachers have higher educational credentials (Magnuson and Waldfogel 2005), which help them to be more sensitive to individual children's needs (Loeb et al 2004), and which increases the likelihood that they will talk with the children, and in turn increase their linguistic capacities.…”
Section: Preschool and Childcarementioning
confidence: 99%
“…Another study looking at the connection between type of childcare and cognitive development was conducted by Loeb et al (2004). The researchers performed a longitudinal analysis of low-income children (12-42 months old) whose mothers were being required to work due to welfare reform (i.e., the Temporary Assistance to Needy Families (TANF) policy).…”
Section: Preschool and Childcarementioning
confidence: 99%
See 1 more Smart Citation